2023
DOI: 10.3390/jpm13030493
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Oesophageal Disease with Cytomegalovirus Infection: A Case Report

Abstract: Immunoglobulin G4-related disease (IgG4-RD) is a fibrous inflammatory process related to immunomodulation. The involvement of the pancreato-biliary tract, retroperitoneum/aorta, head and neck, and salivary glands are the most frequently observed disease phenotypes, differing in their epidemiological features, serological findings, and prognostic outcomes. IgG4-RD was combined with oesophageal ulcers, and the patients were infected with cytomegalovirus at the time of the examination. This constituted a huge cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…However, the impact of EoE on the esophagus has not been as thoroughly understood as its effects on other organs. Nevertheless, case reports and studies have indicated possible involvement [14]. A shared characteristic of the clinical progression in both IgG4-related disease and EoE is their propensity to induce tissue fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of EoE on the esophagus has not been as thoroughly understood as its effects on other organs. Nevertheless, case reports and studies have indicated possible involvement [14]. A shared characteristic of the clinical progression in both IgG4-related disease and EoE is their propensity to induce tissue fibrosis.…”
Section: Introductionmentioning
confidence: 99%